2008
DOI: 10.1080/13814780802436150
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and the presentation of minor illnesses: Data from a 30-year follow-up in general practice

Abstract: Compared to controls, more patients with depression and anxiety disorder present minor illnesses. This could be due to their high attendance rate, altered illness behaviour, or to factors--e.g., stress--underlying both the development of depression or anxiety and the susceptibility to diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…[11][12][13][14][15] As a result of this comorbidity, patients with depression or anxiety are intensive users of medical care. 11,15 The long-term prognosis of depression and anxiety is generally poor, with a substantial proportion of patients not recovering and with many recurrences; the initial severity is an important predictor. [16][17][18][19][20][21][22][23] Regarding the long-term presentation of depression in general practice, it has been reported that about 40% of patients have a recurrence of depression in general practice within a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] As a result of this comorbidity, patients with depression or anxiety are intensive users of medical care. 11,15 The long-term prognosis of depression and anxiety is generally poor, with a substantial proportion of patients not recovering and with many recurrences; the initial severity is an important predictor. [16][17][18][19][20][21][22][23] Regarding the long-term presentation of depression in general practice, it has been reported that about 40% of patients have a recurrence of depression in general practice within a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 From cross-sectional studies, [4][5][6][7][8][9][10] it is known that not all mental health conditions are recognised in general practice, partly because psychiatric and somatic comorbidity are common. [11][12][13][14][15] As a result of this comorbidity, patients with depression or anxiety are intensive users of medical care. 11,15 The long-term prognosis of depression and anxiety is generally poor, with a substantial proportion of patients not recovering and with many recurrences; the initial severity is an important predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Boundaries of syndromal diagnoses are relatively 'soft' and therefore include much overlap and co-morbidity (Mergl et al, 2007;Regier et al, 1990). More than 50% of patients with common mental disorders visit general practitioners with physical, rather than psychological or emotional, complaints (Haftgoli et al, 2010;Hartman et al, 2008). Furthermore, 75% of patients presenting with depression have also anxiety and/ or somatisation (Lowe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have long duration with many assessments (i.e., more than 10 repeated measurements) (Harrison et al 2001;Hartman et al 2008). Recently, with the rapid development of technology-based behavioral health interventions, technological tools, such as mobile devices (e.g., wearable sensors, smartphones) capture real-world and real-time assessments (e.g., ecological momentary assessment) data with abundant observations (Marsch 2012;Ramsey 2015).…”
Section: Introductionmentioning
confidence: 99%